Changes in computed tomography perfusion parameters and maximum contrast enhancement in patients having hydrocephalus with a ventriculoperitoneal shunt: a pilot study. (October 2022) - Lee, Dongjun; Kim, Eun Soo; Lee, Yul; Lee, Sang Min; Yoon, Dae Young; Ju, Young-Su; Chang, In-Bok
Background: Acute hydrocephalus may decrease cerebral perfusion by increasing intracranial pressure. Computed tomography perfusion (CTP) has become a significant adjunct in evaluating regional and global cerebral blood flow (CBF). Purpose: To investigate the changes in cerebral perfusion parameters and maximum contrast enhancement (MCE) in patients with hydrocephalus with ventriculoperitoneal shunt (VPS). Material and Methods: We performed brain CTP in 45 patients, including those with subarachnoid hemorrhage (SAH)-induced hydrocephalus with VPS (n = 14, G1), hydrocephalus (not related to SAH) with VPS (n = 11, G2), SAH-induced hydrocephalus without VPS (n = 10, G3), and hydrocephalus (not related to SAH) without VPS (n = 10, G4). We measured the cerebral perfusion in the frontal white matter (FWM), centrum semiovale, basal ganglia (BG), and eight cortical lesions of interest and compared the differences in CTP parameters among the groups. Results: Between the four groups, cerebral blood volume and MCE in the left FWM and CBF in the right FWM increased significantly in G1 and G2 who underwent VP shunt compared to G3 and G4, whereas perfusion significantly reduced in G3 and G4 who did not undergo VP shunt compared to G1 and G2. MCE in the left BG significantly increased in G2 and decreased in G3 and G4. SAH-induced hydrocephalus showed a lower perfusion than hydrocephalus (not related to SAH) in FWM. Conclusions: Perfusion changes in patients with hydrocephalus after VP shunt were seen in the FWM and BG, which appears to be the result of the hydrocephalus reducing brain perfusion in the deep part of the brain. We concluded that SAH slows brain perfusion recovery.